PENDEKATAN TEORI ABRAHAM MASSLOW SEBAGAI MODEL PEMBINAAN BAGI PENDIDIKAN ANAK USIA REMAJA DI ERA DIGITAL - Yusak Noven Susanto (Metanoia, 2022)
The hierarchy of needs theory put forward by Abraham Maslow is a very familiar theory. Where this theory from the beginning formulated by Abraham Masslow is still relevant and can be implemented in the world of education. The development of digitalization today has made every teenager very vulnerable to being influenced by bad things. This is evidenced by several cases related to juvenile delinquency that occurred using digital media. Through a qualitative approach with descriptive methods, researchers want to know the approach of implementing Abraham Masslow's theory as a coaching for Adolescent Childhood Education in today's digital era.